Cut-down outperforms complete percutaneous transcatheter valve implantation. (February 2018) - Mach, Markus; Wilbring, Manuel; Winkler, Bernhard; Alexiou, Konstantin; Kappert, Utz; Delle-Karth, Georg; Grabenwöger, Martin; Matschke, Klaus
Background: The ideal approach for transfemoral transcatheter aortic valve implantation is still widely debated. The objective of this study was to compare access and bleeding complications of complete percutaneous versus the surgical cut-down approach for transfemoral transcatheter aortic valve implantation. Methods: The study included 667 consecutive patients from November 2008 to December 2016, 466 in the percutaneous group and 201 in the cut-down group. There were no significant differences in baseline characteristics between the 2 groups. Primary study endpoints were vascular access site and bleeding complications according to the Valve Academic Research Consortium II criteria. Results: Mean procedure time was shorter in the cut-down group: 93.5 ± 22.0 (percutaneous) vs. 69 ± 19 min (cut-down), p < 0.001. The rate of access complications was higher in the percutaneous group: 20.4% (95/466) vs. 8.5% (17/201), p = 0.037; with predominantly minor complications in the percutaneous cohort: 14.4% (67/466) vs. 2.5% (5/201), p = 0.04. Bleeding complications were more frequent in the percutaneous group: 21.9% (102/466) vs. 4.5% (9/201), p = 0.01. Hospital mortality was 5.2% in the percutaneous group and 1.9% in the cut-down group ( p = 0.075). Conclusions: Surgical cut-down provided controlled access and resulted in fewer access site and bleeding complications. Nonetheless, major access complications were not significantly different between the two cohorts. The two approaches must be seen as complementary techniques. A portfolio containing both techniques is the only way to provide a tailor-made and patient-orientated approach ensuring the safest access based on the individual vessel condition.